Pengaruh Kerajinan Kerja terhadap Kinerja Karyawan - achmad; Arief Nurdiannova Qurochman; Dani Rohmati (MAPAN: Jurnal Manajemen Akuntansi Palapa Nusantara, 2025)
This study aims to analyze the influence of Crafts on Employee Performance on CVs. GS in Sidoarjo. The research method used was quantitative with a sample of 35 respondents. Data were collected through a Likert scale questionnaire and analyzed using simple linear regression, classical assumption tests, and hypothesis testing (t-test and F-test). The results of the study show that the variable instruments are valid and reliable, and meet the assumptions of normality and heteroscedasticity. The empirical findings show the value of the t-count (8.452) > the t-table (2.034) with a significance of 0.000, so H1 is accepted. Crafts contributed 68.4% to employee performance. In conclusion, Crafts have a significant and positive effect on Employee Performance on CVs. GS. Increasing structural, social, and work challenge management resources are key factors in optimizing company productivity.